Dinamika Keberadaan Allah Tritunggal Secara Teologis dan Signifikansinya bagi Iman - Messakh, Jacob (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
The polemic about being God has a long history of struggle. It has implications for the knowledge and basis of living together. Christianity is called to preach the One God and His actions from creation to human salvation. The doctrinal core is in grace and nature. And both of them cannot be separated from God's being. Aristotle's philosophy is a differentiator in understanding God's being. And the impact is distinguished by God's being through the philosophical method category developed by Thomas Aquinas. While the initial emphasis in opposing Arian through the council of Niceae was wrong in understanding 1 Cor 1:24 with regard to being Jesus Christ the Son who was different from Arian from being God. By Augustine and the Western and Eastern consensus adhering to the relational ousia (being) of God from the start and His actions in salvation are essential and inseparable. Abstrak Polemik tentang keberadaan Allah memiliki sejarah pergulatan panjang. Berimplikasi kepada pengetahuan dan dasar hidup bersama. Kekristenan dipanggil untuk memberitakan Allah yang Esa dan tindakan-Nya sejak penciptaan hingga keselamatan manusia. Inti doktrinalnya pada anuegrah dan alam. Dan keduanya tidak dapat dipisahkan dari keberadaan Allah. Filsafat Aristoteles menjadi pembeda dalam memahami keberadaan Allah. Dan dampaknya dibedakan keberadaan Allah melalui metode filsafat kategori yang dikembangkan Thomas Aquinas. Sementara penekanan awal dalam menentang Arian melalui konsili Niceae karena keliru dalam memahami 1 Kor 1:24 berkenaan dengan keberadaan Yesus Kristus Sang Anak yang oleh Arian berbeda dengan keberadaan Allah. Oleh Agustinus dan consensus Barat dan Timur berpegang kepada ousia (being) Allah yang relational sejak semula dan tindakanNya dalam keselamatan merupakan hal hakiki dan tidak dapat dipisahkan.